Study of the degradation of chlorpyrifos in contaminated soils in the presence of the red california earthworm Eisenia foetida - Ramírez-Revilla, Stamber Álvaro Stamber (2020)
Pesticides containing organophosphorus compounds, such as chlorpyrifos (CPF), are frequently used in agricultural activities, and their use has been increasing due to the presence of multiple plant diseases which threaten the production of vegetable food products. As a result of this practice, the soils in question are often found to be contaminated due to the fact that these pesticides do not immediately degrade and hence remain for long periods of time. The objective of this study was to evaluate the degradation of CPF in the presence and absence of the worm Eisenia foetida (EF) in soils contaminated with 40 mg/kg of CPF during a 28-day period. The D group, whose soil was sterilized and in which no EF worms were present, yielded a CPF-degradation result of 33.68 %. The C group, in which the soil was unsterilized and there were no EF worms present, yielded a degradation percentage of 37.16 %. On the other hand, the B group, containing sterilized soil in which the EF worms were present, yielded a degradation percentage of 60.76 %. Finally, with the A group, in which the soil was unsterilized and EF worms were present, degraded in 74.85 %.